ECONOMIC SUPPLY OF INNOVATION TECHNOLOGIES FOR THE DEVELOPMENT OF CARBON HEALTH CARE WITH OIL-WEIGHTED SPARE PARTS - Pilka, M. S. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
T The possibilities of attraction of investments for efficient removal of hydrocarbon reserves, which belong to hardrecoverable and mechanisms for attracting investments in the further development of oil and gas deposits in Ukraine, are presented. The main principles of the ranking of hydrocarbon reserves are considered, deposits structure analysis is needed to evaluate the prospects of transferring their parts to cost-effective ones if some economic conditions will change, as well as the appearance of new methods and technologies for attracting these reserves into development. For oil and gas companies information about the qualitative characteristics of profitable reserves and their distribution in the collectors is very important. The main advantages of using intelligent oil and gas field technologies, which enable real-time realization of fast processing of large volumes of geological information, modeling of various extraction scenarios, and the adoption of rational management decisions for optimizing oil and gas production are described. Hydrodynamic modeling, as an instrument for the search and growth of hydrocarbon reserves, its quantitative and qualitative assessment and a detailed comprehensive study of productive collectors based on modern achievements in geological and geophysical sciences is one of the main ways of development of hardrecoverable reserves. The application of existing and the creation of new technological solutions for the efficient production of oil and gas with positive economic indicators, is a logical continuation of a complex of works on low-yielding hydrocarbon deposits. The main source of growth of hydrocarbon reserves in deposits with a long history of development are: unidentified reserves outside the productive part of the deposit and missed oil-saturated intervals; oil-saturated intervals in the productive section, which aren’t attracted in the development. The development of hardrecoverable reserves is associated with considerable complexity, but the engineering approach, using development monitoring, hydrodynamic modeling, attracting international experience and new technologies, will increase profitability and obtain additional extraction of significant volumes of hydrocarbons, which will ensure not only the achievement of maximum investment efficiency, but also full usage of natural resources of hydrocarbons.